2019
DOI: 10.1017/s1355617719000444
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methylphenidate on Long-Term Neuropsychological and Everyday Executive Functioning After Traumatic Brain Injury in Children with Secondary Attention Problems

Abstract: Objective: To investigate the effects of methylphenidate on long-term executive and neuropsychological functioning in children with attention problems following TBI, as well as the relationship between methylphenidate associated changes in lab-based neuropsychological measures of attentional control, processing speed, and executive functioning and parent- or self-report measures of everyday executive functioning. Method: 26 children aged 6–17 years, who were hospitalized for moderate-to-severe blunt head traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Among the most common cognitive consequences, significant attention deficits were reported in about 35% of children within two years of their TBI (Max et al, 2005), and were observed to strongly contribute to elevated risk for severe psychopathology and impairments in overall functioning in late adolescence, with the pathophysiological underpinning yet to be fully elucidated (Le Fur et al, 2019;Narad et al, 2019). The post-TBI attention problems in children have been evaluated and treated based on endorsements of behavioral symptoms from subjective observations, and have resulted in largely divergent results regarding effectiveness (Backeljauw and Kurowski, 2014;Kurowski et al, 2019;LeBlond et al, 2019). Understanding the neurobiological substrates of post-TBI attention deficits in children is thus vitally critical, so that timely and tailored strategies can be developed for diagnoses and long-term treatments and interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common cognitive consequences, significant attention deficits were reported in about 35% of children within two years of their TBI (Max et al, 2005), and were observed to strongly contribute to elevated risk for severe psychopathology and impairments in overall functioning in late adolescence, with the pathophysiological underpinning yet to be fully elucidated (Le Fur et al, 2019;Narad et al, 2019). The post-TBI attention problems in children have been evaluated and treated based on endorsements of behavioral symptoms from subjective observations, and have resulted in largely divergent results regarding effectiveness (Backeljauw and Kurowski, 2014;Kurowski et al, 2019;LeBlond et al, 2019). Understanding the neurobiological substrates of post-TBI attention deficits in children is thus vitally critical, so that timely and tailored strategies can be developed for diagnoses and long-term treatments and interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the meta-analytic effect was replicated when including only the higher-quality studies with low risk of bias. 44,45,47,48,54 (d = 0.185, 95% CI: 0.028-0.341, P = 0.021). Finally, we found no evidence for publication bias in the visual inspection of the Funnel plot and Egger's Regression intercept (P = 0.15).…”
Section: Main Analysismentioning
confidence: 98%
“…The attention problems in children post-TBI can persist into late adolescence and have been linked to the development of severe psychopathology and impairments in overall functioning (Le Fur et al, 2019;Narad et al, 2019). Without having established neurobiological signatures, treatments and interventions of TBI-related attention deficits in children have been based on subjective observations from clinicians and have resulted in suboptimal efficacy (Backeljauw and Kurowski, 2014;Kurowski et al, 2019;LeBlond et al, 2019).…”
Section: Introductionmentioning
confidence: 99%